The killings at Kingfisher Hill - Hannah, Sophie, 1971-; Christie, Agatha, 1890-1976 (Hannah, Sophie, 1971- Hercule Poirot mysteries, 2020)
"Hercule Poirot is traveling by luxury passenger coach from London to the exclusive Kingfisher Hill estate. Richard Devonport has summoned the renowned detective to prove that his fiancée, Helen, is innocent of the murder of his brother, Frank. Poirot will have only days to investigate before Helen is hanged, but there is one strange condition attached: he must conceal his true reason for being there from the rest of the Devonport family. The coach is forced to stop when a distressed woman demands to get off, insisting that if she stays in her seat, she will be murdered. Although the rest of the journey passes without anyone being harmed, Poirot's curiosity is aroused, and his fears are later confirmed when a body is discovered with a macabre note attached... Could this new murder and the peculiar incident on the coach be clues to solving the mystery of who killed Frank Devonport? And if Helen is innocent, can Poirot find the true culprit in time to save her from the gallows?"--